2012
DOI: 10.2215/cjn.07080712
|View full text |Cite
|
Sign up to set email alerts
|

How to Overcome Barriers and Establish a Successful Home HD Program

Abstract: Summary Home hemodialysis (HD) is an underused dialysis modality in the United States, even though it provides an efficient and probably cost-effective way to provide more frequent or longer dialysis. With the advent of newer home HD systems that are easier for patients to learn, use, and maintain, patient and provider interest in home HD is increasing. Although barriers for providers are similar to those for peritoneal dialysis, home HD requires more extensive patient training, nursing education, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 90 publications
1
65
0
2
Order By: Relevance
“…One of the persistent barriers to greater adoption of home HD is the need for patients or caregivers to perform frequent cannulation of arteriovenous (AV) access (fistula or graft) (6)(7)(8). Data from the Frequent Hemodialysis Network Trial have also shown a higher incidence of interventions on AV access with higher frequency of use as occurs with home HD (9).…”
Section: Introductionmentioning
confidence: 99%
“…One of the persistent barriers to greater adoption of home HD is the need for patients or caregivers to perform frequent cannulation of arteriovenous (AV) access (fistula or graft) (6)(7)(8). Data from the Frequent Hemodialysis Network Trial have also shown a higher incidence of interventions on AV access with higher frequency of use as occurs with home HD (9).…”
Section: Introductionmentioning
confidence: 99%
“…In some European countries, up to 40% of patients receive this type of dialysis, with access to this modality increasing. Portugal is also expanding the service; in the United States and Canada, there are studies that have assessed the differences in costs and quality of life resulting from these different modalities of dialysis 31,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Doctors may not offer patients the procedure due to this. In relation to patients, the level of schooling, understanding their health condition, family involvement, and the physical and hygienic conditions in the household need to be considered before deciding the appropriate treatment 31,32,35 .…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In published reports and cumulative clinical experience, the number of sessions needed to complete training requirements is 20-40 sessions, but occasionally more may be needed (see the supplement article, "Patient Selection and Training for Home Hemodialysis"). [8][9][10][11][12][13][14][15] In the anecdotal experience of the authors, the duration of training tends to be consistent across countries: those with a lower prevalence of home HD, such as the United States, report a lower number of home HD training sessions (<30) than countries with a higher prevalence of home HD patients, such as New Zealand (>30).…”
Section: Number Of Home Hd Training Stations To Support the Programmentioning
confidence: 99%